2018
DOI: 10.1371/journal.pone.0196515
|View full text |Cite
|
Sign up to set email alerts
|

Altered dopaminergic regulation of the dorsal striatum is able to induce tic-like movements in juvenile rats

Abstract: Motor tics are sudden, repetitive, involuntary movements representing the hallmark behaviors of the neurodevelopmental disease Tourette’s syndrome (TS). The primary cause of TS remains unclear. The initial observation that dopaminergic antagonists alleviate tics led to the development of a dopaminergic theory of TS etiology which is supported by post mortem and in vivo studies indicating that non-physiological activation of the striatum could generate tics. The striatum controls movement execution through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 83 publications
1
24
0
1
Order By: Relevance
“…As the CTOC sample is predominantly composed of specialized and tertiary health services, the recruitment of more severe patients, nonresponders to conventional and complex treatments (with comorbidities with tics, for example), may have biased our results, leading to a greater prevalence of the use of these specific medications in these centers (39, 42, 85). As poor insight was related to sensory phenomena, and since sensory phenomena are more prevalent in patients with OCD who also have tics (64, 86), we could speculate a “dopaminergic” modulation of “poor insight.” It could be explained by the facts that tics occur due to dopaminergic dysfunctions involving the basal nuclei, especially striatum and substantia nigra (87, 88), which may result clinically in the increased prescription of drugs with dopaminergic action, such as neuroleptics. Thus, the association of an atypical neuroleptic with SSRIs could act, in these cases, with synergism by serotonergic potentiation or with synergism by addition, adding effect in the involved dopaminergic neurocircuits.…”
Section: Discussionmentioning
confidence: 99%
“…As the CTOC sample is predominantly composed of specialized and tertiary health services, the recruitment of more severe patients, nonresponders to conventional and complex treatments (with comorbidities with tics, for example), may have biased our results, leading to a greater prevalence of the use of these specific medications in these centers (39, 42, 85). As poor insight was related to sensory phenomena, and since sensory phenomena are more prevalent in patients with OCD who also have tics (64, 86), we could speculate a “dopaminergic” modulation of “poor insight.” It could be explained by the facts that tics occur due to dopaminergic dysfunctions involving the basal nuclei, especially striatum and substantia nigra (87, 88), which may result clinically in the increased prescription of drugs with dopaminergic action, such as neuroleptics. Thus, the association of an atypical neuroleptic with SSRIs could act, in these cases, with synergism by serotonergic potentiation or with synergism by addition, adding effect in the involved dopaminergic neurocircuits.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been 150 articles in PUBMED, and the SAGE Encyclopedia of Abnormal and Clinical Psychology published a definition in 2017 ( 8 ). The RDS concept arose from the findings that dysfunction in the dopaminergic system are implicated in reward mechanisms in the brain and lead to substance seeking behavior and non-substance addictive behaviors ( 7 ) like pathological gambling ( 9 11 ), Tic Disorders ( 12 , 13 ), Tourette's syndrome ( 14 ), and attention deficit hyperactivity disorder (ADHD) ( 15 17 ).…”
Section: Reward Deficiency Syndrome (Rds)mentioning
confidence: 99%
“…Dopamine (DA) is a neurotransmitter that can regulate neural processes including motor control, cognition, and memory (Chun et al, 2013). Previous studies have suggested that the imbalanced expression of DA plays an important role in the development of TS (Nespoli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%